2018
DOI: 10.1089/end.2017.0853
|View full text |Cite
|
Sign up to set email alerts
|

Monopolar Transurethral Enucleo-Resection of the Prostate Versus Holmium Laser Enucleation of the Prostate: A Canadian Novel Experience

Abstract: In this study, TUERP was safe and efficacious in benign prostatic hyperplasia patients with large glands. Modifications can be implemented on the standard transurethral resection of the prostate technique to treat patients with prostate sizes >70 cc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Khaled and his colleagues retrospectively analyzed the change of PSA in patients undergoing TURP and HoLEP, and found that the level of serum PSA dropped more in HoLEP group. [17] Nielsen et al found that PSA released after prostatectomy was associated with an increase in postoperative PF1+2 and TAT. [14] This may be due to the fact that the PSA is structurally and functionally very similar to the protein that activates the clotting reaction, since they all belong to the serine protease family, [18] although underlying mechanism is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Khaled and his colleagues retrospectively analyzed the change of PSA in patients undergoing TURP and HoLEP, and found that the level of serum PSA dropped more in HoLEP group. [17] Nielsen et al found that PSA released after prostatectomy was associated with an increase in postoperative PF1+2 and TAT. [14] This may be due to the fact that the PSA is structurally and functionally very similar to the protein that activates the clotting reaction, since they all belong to the serine protease family, [18] although underlying mechanism is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…After removal of duplicates, 258 articles were reviewed based on title and abstract. Eighty-one articles underwent full-text review, and 57 studies were finally included [9‒65] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…The complications and short-term results in terms of IPSS, Qmax and PVR were similar. They reported complications like TUR syndrome and excessive bleeding with larger prostates, which were not issues in the studies of Ajib [ 20 ] and Pansadoro [ 18 ]. They found that the learning curve of monopolar enucleation was slightly higher than HOLEP but concluded that monopolar enucleation is a relatively safer procedure as no serious complications were encountered during the early learning curve.…”
Section: Discussionmentioning
confidence: 99%
“…Ajib [ 20 ] described the TUERP technique in comparison with HOLEP in 2019 (24 vs. 27 cases); they resected the median lobe in a similar manner to TURP and then enucleated the lateral lobes. If the lobes were completely enucleated, they was morcellated or else resected with a loop.…”
Section: Discussionmentioning
confidence: 99%